Peran Edukasi Dalam Mencegah Tindakan Bullying Di Kalangan Siswa SD Negeri 08 Indudur, IX Koto Sungai Lasi - Fatimah; Leni Zahara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Bullying is a serious problem that often occurs in elementary schools and can have a negative impact on children's psychological and social development. For this reason, Real Work Lecture (KKN) students from Padang State University conducted prevention activities through counseling and education about the dangers of bullying at SD Negeri 08 Indudur, IX Koto Sungai Lasi, Solok Regency. This activity aims to increase students' understanding of the definition and types of bullying, its impact on victims and perpetrators, and how to prevent and respond to bullying cases in the area and around the school. This activity uses an interactive presentation method with a participatory and educational approach. Based on the results of the activity, it shows that this education and counseling contributes to increasing students' awareness and understanding of bullying, thus helping to create a safer, more comfortable and friendly school atmosphere for all students.